2005
DOI: 10.1007/s11270-005-0083-6
|View full text |Cite
|
Sign up to set email alerts
|

Can We Use Zebra and Quagga Mussels for Biomonitoring Contaminants in the Niagara River?

Abstract: We compared contaminants in zebra and quagga mussels (Dreissena polymorpha and Dreissena bugensis) of two different size classes from sites within the Niagara River to determine if the two species and two size classes can be used to monitor contaminants. Composite samples (i.e., at least 50 individuals) were analysed for 7 trace metals, total PCBs, selected organochlorine pesticides, chlorinated benzenes, and dioxins and furans. ANOVAs and MANOVAs showed that metal tissue concentrations varied significantly am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 34 publications
1
18
1
Order By: Relevance
“…This implies that larger/older mussels even at relatively 43 low pollution pressure are more affected by chemical stress than smaller individuals. 1 Additionally, at relatively low concentration of pollutants the higher growth dilution 2 characteristic for younger individuals may partially reduce the accumulation rates of 3 pollutants as reported by Richman and Somers (2005). 4 Biomarker responses of D. bugensis samples obtained from the slightly polluted habitats of 5 Lake Balaton showed strong seasonality and size-dependent correlation in October, 6 coinciding with the end of the shipping season.…”
Section: (2014) 27mentioning
confidence: 91%
See 1 more Smart Citation
“…This implies that larger/older mussels even at relatively 43 low pollution pressure are more affected by chemical stress than smaller individuals. 1 Additionally, at relatively low concentration of pollutants the higher growth dilution 2 characteristic for younger individuals may partially reduce the accumulation rates of 3 pollutants as reported by Richman and Somers (2005). 4 Biomarker responses of D. bugensis samples obtained from the slightly polluted habitats of 5 Lake Balaton showed strong seasonality and size-dependent correlation in October, 6 coinciding with the end of the shipping season.…”
Section: (2014) 27mentioning
confidence: 91%
“…For in situ pollution assessment of freshwater habitats bivalves, including the zebra mussel 6 (Dreissena polymorpha) proved to be suitable bioindicator organisms due to their widespread 7 distribution, sedentary and filter-feeding nature and their fairly good tolerance to physico- invasion of quagga mussel (Dreissena bugensis) in the last decades which shifted their 13 dominance over the formerly established zebra mussel populations (Mills et al 1996; Bij de 14 Vaate et al 2014), therefore, the already established biomarker assays should be performed on 15 this new species as well. 16 Based on the wealth of knowledge of previous researches of the field, the main goal of our 17 study was to provide data by the in situ assessment on: i. the seasonal variability of selected 18 biomarkers, known to be influenced by reproductive cycle, temperature, food availability and 19 quality.…”
Section: Introduction 24mentioning
confidence: 99%
“…However, the widespread invasion of the quagga mussel (Dreissena rostriformis bugensis), resulting in an overgrowth of the quagga mussels within dreissenid populations (Mills et al, 1996;Bij de Vaate et al, 2014) calls for knowledge on the modulation of the routinely used biomarkers also in quagga mussels in response to anthropogenic pollutants. Interspecies differences in bioaccumulation of pollutants for the two dreissenid species have already been reported (Richman and Somers, 2005;Mathews et al, 2015). This variability was thought to be related to differences in both habitat preference characteristics and in physiological attributes of the two species such as energy consumption, filtration-and growth rate (Veltman et al, 2008;Le et al, 2011).…”
Section: Introductionmentioning
confidence: 65%
“…D. bugensis was proven to allocate more energy to soft tissue relative to shell length (Roe and MacIsaac, 1997), has higher assimilation efficiency (Baldwin et al, 2002), grows faster (Baldwin et al, 2002;Karatayev et al, 2011;Le et al, 2011), filters at a higher rate (Diggins, 2001;Veltman et al, 2008) and was reported to have a lower respiration rate (Stoeckmann, 2003). Interspecies differences were also found for the accumulation of metals and organic contaminants, in general with higher contaminant burdens in D. polymorpha (Rutzke et al, 2000;Richman and Somers, 2005;Schäfer et al, 2012;Matthews et al, 2015). In the meantime, while several studies have addressed the interspecies variability in biomarker responses to chemical stress in different aquatic invertebrates, in the case of dreissenids these issues have seldom been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a shift in dominance from established to newly invading mussel species may alter the trophic transfer of metals to native predators. Peer reviewed literature focussing on potential differences in accumulation of metals between the soft tissues of the quagga and zebra mussel is scarce, often inconclusive and limited to North America (Johns and Timmerman, 1998;Rutzke et al, 2000;Richman and Somers, 2005;Le et al, 2011). Moreover, studies reporting metal concentrations in quagga mussels are particularly rare.…”
Section: Introductionmentioning
confidence: 99%